DIPLOMASI DAN HUBUNGAN LUAR NEGERI PEMERINTAH DAERAH - Suryo, Herning (Transformasi, 2012)
Abstract Â  In Indonesia Act - Act No. 37 of 1999 on Foreign Relations, Law No. 24 of 2000 on International Treaties and Law No. 32 Year 2004 on Regional Autonomy, has authorized local governments to conduct foreign relations with other countries in various fields of work together, such as trade, economic investment, tourism, agriculture, education and the environment in order to promote regional development, improve local economies and increase revenue, which in turn will bring wealth and prosperity to the area. Understand the situation and make the local authority should be more excited to be able to further enhance cooperation on overseas, and start thinking about what measures to be done in local government welcomes the challenges and opportunities in Law No. 37 of 1999 and Act No. 32 of 2004 . Keyword : Diplomacy; Foreign Relations Â